Identification of new species record of Cyanophyceae in Diyala River, Iraq based on 16S rRNA sequence data (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hassan FM, Mahdi WM, Al-Haideri HH, Kamil DW. 2022. Identification of new species record of Cyanophyceae in Diyala River, Iraq based on 16S rRNA sequence data. Biodiversitas 23: 5239-5246. The biodiversity and water quality of the Diyala River require screening water in terms of biological contamination, because it is the only water source in Diyala City and is used for many purposes. This study aimed to identify a new species record of Cynaophyceae and emphasize the importance of using molecular methods beside classic morphological approaches, particularly in the water-shrinkage-aqua system. Five different sites along Diyala River were selected for Cyanophyceae identification. Morphological examination and 16S rRNA sequence analysis was conducted, and the phylogenetic tree was constructed using Mega 6 Programme. The morphological examination of samples showed a total of 28 species corresponds to Cyanophyceae, including one species of Spirulina. In our study of 28 identified species, three new species record were identified in Diyala River. The newly recorded species were confirmed by 16S rRNA and the phylogenetic tree construction. The species are registered in the National Centre for Biotechnology Information (NCBI) with the following accession numbers: Arthrospira indica (MW854667.1), Arthrospira platensis (MW854665.1), and Limnospira fusiformis (MW854666.1). Most notably, Arthrospira platensis is not listed in the checklist of Iraqi algae. Thus, these species are considered as a new record of Iraqi algal flora. The identification of new species record in Diyala River reflexes the impact of climate change on this river, and the necessity to use 16S rRNA to identify microalgae in all ecosystems.
Keywords: 16S rRNA, Cyanophyceae, Diyala River, phylogenetic tree